Penerapan Metode PQ4R untuk Meningkatkan Pemahaman Membaca Siswa Sekolah Dasar - Rachel Ananda Anastasya Putri; Ahmad Nurefendi Fradana (JPDI (Jurnal Pendidikan Dasar Indonesia), 2026)
This study aims to describe the application of the PQ4R (Preview, Question, Read, Reflect, Recite, Review) method in improving elementary school students' reading comprehension skills. The study was conducted descriptively qualitatively with subjects of teachers and fifth grade students of SD Muhammadiyah 5 Porong. Data were collected through observation, interviews, and documentation. The results showed that the systematic application of the PQ4R method can increase student engagement, strengthen memory, and help them understand the contents of the reading better. Each stage in the PQ4R method plays an important role in encouraging critical and reflective thinking. In addition, there was an increase in student learning motivation, the ability to formulate questions, and convey reading summaries independently. Thus, PQ4R has proven effective as an Indonesian language learning strategy to improve reading comprehension skills at the elementary school level.